The Effect of Kirigami Activities on Fine Motor Skills in Group B Children - Natasya , Claulia; Oktamarina, Lidia; Handayani, Tutut (JURNAL PENA PAUD, 2025)
The inadequate fine motor skills of young children, particularly in the areas of cutting, folding, and drawing, are the driving force for this study. One of the contributing reasons is the absence of constant and interesting stimulation. Kirigami activities, which involve folding and cutting, are believed to improve children's fine motor skills. This study used a pre-experimental one-group pretest-posttest design and a quantitative methodology. There were 34 children in group B at Bintang Kembar Kindergarten when the study was carried out. 16 kids who displayed delays in fine motor abilities were chosen for the sample using purposive sampling at the teacher's recommendation. Tests, documentation, and observation were used to gather data. Validity, reliability, normalcy, homogeneity, and paired sample t-test tests were all used in the data analysis. The findings demonstrated that kirigami activities significantly improved children's fine motor abilities. This is evidenced by a t-value of -27.571. With a degree of freedom (df) = 15 and a significance level of 5% (0.05), the critical t-value is ±2.131. Since the absolute value of the t-calculated is greater than the t-table value (|−27.571| > 2.131), the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. This indicates that the kirigami activity has a significant effect on improving the fine motor skills of Group B children at TK Bintang Kembar.